Inovasi Produk Dan Mesin Cetak Briket Biomassa Dari Limbah Serbuk Kayu UMKM Mebel “Sumber Rezeki” di Desa Candiwatu, Kecamatan Pacet, Kabupaten Mojokerto - Julia Azzahra, Nadya Shavira; Ramadhani, Eko Saputra; Alaziz, Ilham Sandhy; Pratama, Rivaldi Yoga; Sri Diyanti, Daffa Dwi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Small and Medium Enterprises (SMEs) in the furniture industry, particularly "Sumber Rezeki" furniture SMEs in Candiwatu Village, face significant challenges in managing wood sawdust waste, which often accumulates without proper utilization. This community service project introduces an innovative biomass briquette pressing machine made from locally available materials to convert sawdust waste into valuable fuel briquettes. Developed through participatory action research methodology, the machine demonstrates remarkable efficiency in waste reduction by converting 95% of sawdust waste into usable briquettes. Field testing shows the machine can produce 50 briquettes per hour with consistent quality and 4,500 kcal/kg heating value. The technology supports sustainable waste management while creating additional income streams for furniture SMEs, reducing environmental impact and promoting circular economy principles.